2016
DOI: 10.1007/s13181-016-0595-z
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Hyperemesis Syndrome: Diagnosis, Pathophysiology, and Treatment—a Systematic Review

Abstract: Cannabinoid hyperemesis syndrome (CHS) is a syndrome of cyclic vomiting associated with cannabis use. Our objective is to summarize the available evidence on CHS diagnosis, pathophysiology, and treatment. We performed a systematic review using MEDLINE, Ovid MEDLINE, Embase, Web of Science, and the Cochrane Library from January 2000 through September 24, 2015. Articles eligible for inclusion were evaluated using the G r a d i n g a n d R e c o m m e n d a t i o n s A s s e s s m e n t , Development, and Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
246
2
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(296 citation statements)
references
References 142 publications
9
246
2
28
Order By: Relevance
“…Hence, the key to developing effective, personalized treatments for CVS hinges on recognizing disease triggers and mechanisms and raising the individual threshold for developing symptoms. The diversity of pathways may either reflect the presence of specific subtypes of CVS (eg, catamenial, hypothalamic surge, and CHS), distinct genetic predispositions (eg, RYR2 gene encoding a stress‐induced neuronal calcium channel polymorphisms), and/or a sensitivity to distinct symptom triggers (eg, psychological stressors and hypoglycemia) . In order to develop targeted CVS therapies, future research needs to define CVS subtypes based on mechanistic definitions, rather than solely on symptom criteria.…”
Section: Pathophysiology and Comorbid Conditionsmentioning
confidence: 99%
“…Hence, the key to developing effective, personalized treatments for CVS hinges on recognizing disease triggers and mechanisms and raising the individual threshold for developing symptoms. The diversity of pathways may either reflect the presence of specific subtypes of CVS (eg, catamenial, hypothalamic surge, and CHS), distinct genetic predispositions (eg, RYR2 gene encoding a stress‐induced neuronal calcium channel polymorphisms), and/or a sensitivity to distinct symptom triggers (eg, psychological stressors and hypoglycemia) . In order to develop targeted CVS therapies, future research needs to define CVS subtypes based on mechanistic definitions, rather than solely on symptom criteria.…”
Section: Pathophysiology and Comorbid Conditionsmentioning
confidence: 99%
“…In a systematic review of CHS patients, 179 patients, 25.1% reported that they used cannabis for ≤1 year, 36.3% for 2–5 years, 16.8% for 6–10 years, and 21.8% for ≥11 years. In this same study, frequency of cannabis use ( n = 211) was reported as: 23.7% used more than once a day, 47.9% used daily, 19.4% used weekly, 2.4% used less than once a week, and 6.6% did not specify [80]. Just as patients may not disclose their marijuana use, others may admit to “occasional” marijuana use, but downplay its duration or frequency.…”
Section: Resultsmentioning
confidence: 99%
“…Although the clinical toxidromes associated with synthetic cannabinoids can differ from those of natural cannabinoids, synthetic cannabinoids interact with the CB1 receptor [4] and since these cases meet our criteria for CHS diagnosis [5], we believe that these cases should be labeled as CHS and treated as such.…”
mentioning
confidence: 93%